Kedudukan Kaidah Fikih dalam Ijtihad dan Relevansi dengan Kompilasi Hukum Islam (KHI) - Efendi, Johan; Azwar, Zainal (UIN Imam Bonjol Padang, 2019)
This paper intended to examine the position of the juristic conventions in ijtihad and its relevance to the Kompilasi Hukum Islam (KHI) book I on mar- riage. This research is motivated by the fact that al-Qur’an and Hadith are sources in establishing Islamic law, both of which are called mashdar, other le- gal propositions are Ijmâ ‘, Qiyâs, Istihsân, Mashlahah Mursalah,’ Urf, Syar’u man Qablanâ, Qawl al-Shahâbî, Istishâb and Sad al-Dzarî’ah. But in fact the rule of fiqh is also used as a theorem in establishing the law, whereas earlier scholars did not mention the rule of jurisprudence as one of the theorems in establishing Islamic law. So the question of this research is (1) what is the essence of the jurisprudence, (2) how the jurisprudence principle in ijtihad according to the scholars, and (3) how the relevance of the jurisprudence prin- ciple with the Compilation of Islamic Law (KHI) in book 1 on marriage. This research comes to conclusions, namely: (1) the essence of fiqh rule is the words of the ulama (qaul al-mujtahid). (2) The majority of scholars agree to make the jurisprudence as a complementary proposition in the establishment of a law. The juristic jurisprudence can only be used as a complementary argument. (3) There is a strong relevance between the jurisprudence principles that have been formulated by the previous scholars with the Compilation of Islamic Law es- pecially the book 1 on marriage, with the discovery of several articles that are relevant and relevant to the juristic principles